Development of novel Phthalocyanine/Graphene oxide Composite: Potential usage for Sono/Photochemical Applications, and the treatment of type-2 diabetes and Alzheimer's disease - Gunsel, Armagan; Gunsel, Hilal; Atmaca, Goknur Yasa; Taslimi, Parham; Sadeghian, Nastaran; Piskin, Hasan; Bilgicli, Ahmet T.; Gulcin, Lhami; Erdogmus, Ali; Yarasir, M. Nilufer (ELSEVIER SCIENCE SA, 2025)
In this study, the novel 3-(benzo[d]thiazol-2-ylthio) phthalonitrile (1) as starting material was synthesized and its molecular structure was verified by the experiment of single crystal X-ray diffraction, and it was first brought to the literature. Then, its non-peripherally tetra-thiazol derivative-substituted phthalocyninato gallium (III) chloride compound (GaClPc:2) was synthesized and characterized for the first time. Then, GaClPc-GO composites (2a-2c) were prepared by non-covalent interaction between GaClPc (2) and graphene oxide (GO). All compounds used were characterized with various spectroscopic methods such as UV-Vis, FT-IR, 1H NMR, 13C NMR, SEM and MALDI-TOF MS, Raman. The sonochemical, photochemical and sono-photochemical abilities of the synthesized substances were systematically examined by a comprehensive analysis. The recorded measurements showed that remarkably high quantum yields were obtained after sono-photochemical studies, indicating that these sensitizers could be promising candidate sensitizer molecules for use in pioneering cancer therapies. Then, their effects on several metabolic enzymes were investigated and have been found to be effective inhibition against alpha-glycosidase, alpha-amylase, butyrylcholinesterase and acetylcholinesterase. Also, IC50 were found as 5.02 to 11.60 mu M for AChE, 12.05 to 36.52 mu M for BChE, 48.52 to 64.50 mu M for alpha-amylase, and 31.14 and 39.64 mu M for alpha-glycosidase.
Keywords: Phthalocyanine; Crystal structure; Sono/photochemical; Enzyme inhibition; GRAPHENE OXIDE; PHOTODYNAMIC THERAPY; PHOTOPHYSICOCHEMICAL PROPERTIES; BIOLOGICAL EVALUATION; THIAZOLE DERIVATIVES; STRUCTURE VALIDATION; SINGLET OXYGEN; GALLIUM III; DELIVERY; CANCER; Chemistry